Системно значимые банки: критерии идентификации и подходы к регулированию в Kазахстане (Journal of Economic Research & Business Administration, 2022)
In recent decades, we observe the widespread growth of the size of the largest banks, the strengthening of their concentration and the increasing role in the development of national economies. The largest banks are now becoming the most important factor in ensuring the financial stability of both national banking systems and the stability of the global financial system as a whole. In this regard, determination of effective principles and transparent criteria for identifying the so-called "systemically significant banks" and the transition to the practice of differentiated regulation of banking activities became quite an important concern.                The purpose of the article is, firstly, to study both common approaches and to reveal differences in the identification of systemically significant banks of the countries that are members of the Regional Advisory Group of CIS countries, and secondly, to critically analyze and summarize the first experience of differentiated regulation of commercial banks.                To effectively complete the tasks, set in the article, the works of foreign and domestic researchers, regulations and reports of international organizations, as well as reports of the National Bank and the Agency of the Republic of Kazakhstan for Regulation and Supervision of the Financial Market and Financial Organizations have been studied. The research included methods of observation, generalization, logical and statistical analysis, together with comparison. To ensure the long-term sustainability of systemically important banks, all necessary conclusions were made and recommendations were proposed accordingly.Keywords: systemically significant banks, TBTF reforms, banks of Kazakhstan, prudential requirements